2022
DOI: 10.7759/cureus.26295
|View full text |Cite
|
Sign up to set email alerts
|

An Unanticipated Worsening of Glycemic Control Following a Mild COVID-19 Infection

Abstract: We describe a case of acute-onset worsening of a patient's previously well-controlled type 2 diabetes mellitus (T2DM) following his recovery from a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. A 78-year-old male with a three-year medical history of well-controlled T2DM (controlled by diet and metformin) presented to the outpatient clinic to discuss his regularly scheduled six-month lab work. He mentioned having a mild coronavirus disease 2019 (COVID-19) infection lasting one we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Several studies and reports have indicated that severe hyperglycaemia and diabetes mellitus are associated with higher mortality and poor prognosis in COVID-19 patients [ 16 , 17 ]. There is a small amount of data on how mild COVID-19 infection influences glucose level [ 18 , 19 ], and all was obtained from the adult population. Therefore, we aimed to evaluate the association between glycaemia and selected clinical and laboratory features of mild COVID-19 infection and to compare it with other RNA viral respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies and reports have indicated that severe hyperglycaemia and diabetes mellitus are associated with higher mortality and poor prognosis in COVID-19 patients [ 16 , 17 ]. There is a small amount of data on how mild COVID-19 infection influences glucose level [ 18 , 19 ], and all was obtained from the adult population. Therefore, we aimed to evaluate the association between glycaemia and selected clinical and laboratory features of mild COVID-19 infection and to compare it with other RNA viral respiratory infections.…”
Section: Introductionmentioning
confidence: 99%